Changes of professional value orientations of teachers in the system of postgraduate education - Olena Bondarchuk; Hanna Pecherska (Social Welfare: Interdisciplinary Approach)
The paper presents the features of changes in professional value orientations of teachers in the system of postgraduate education. The means implementing the development of the program and change of teachers’ professional value orientations was a special course-training, which provided the impact on cognitive, emotional-evaluative and behavioral components of professional value orientations. Results of the formative experiment demonstrated the possibility of the development of professional value orientations of teachers and effectiveness of the special course-training proposed for professional teacher training in the system of postgraduate education.